2016
DOI: 10.1016/j.agee.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative productivity of alternative cellulosic bioenergy cropping systems in the North Central USA

Abstract: Biofuels from lignocellulosic feedstocks have the potential to improve a wide range of ecosystem services while simultaneously reducing dependence on fossil fuels. Here, we report on the six-year production potential (above ground net primary production, ANPP), post-frost harvested biomass (yield), and gross harvest efficiency (GHE=yield/ANPP) of seven model bioenergy cropping systems in both southcentral Wisconsin (ARL) and southwest Michigan (KBS). The cropping systems studied were continuous corn (Zea mays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 53 publications
3
100
0
Order By: Relevance
“…Moreover, ethanol yields are likely to differ among cropping systems because both biomass production (Sanford et al, 2016) and sugar content (Garlock et al, 2012;Godin et al, 2013) from harvested crops can vary considerably in time and space.…”
mentioning
confidence: 99%
“…Moreover, ethanol yields are likely to differ among cropping systems because both biomass production (Sanford et al, 2016) and sugar content (Garlock et al, 2012;Godin et al, 2013) from harvested crops can vary considerably in time and space.…”
mentioning
confidence: 99%
“…There is some previous evidence to support our finding. Sanford et al (2016) reported that four-year average harvest efficiency increased from 35% in prairie (a mix of graminoids and forbs) to 61% in monoculture switchgrass [20]. However, at another site, the same study reported a mere one percentage point increase in five-year average harvest efficiency from mixed prairie to switchgrass [20].…”
Section: Harvest Efficiency Is Greater In Graminoids Compared To Forbsmentioning
confidence: 89%
“…Sanford et al (2016) reported that four-year average harvest efficiency increased from 35% in prairie (a mix of graminoids and forbs) to 61% in monoculture switchgrass [20]. However, at another site, the same study reported a mere one percentage point increase in five-year average harvest efficiency from mixed prairie to switchgrass [20]. Therefore, while harvest efficiency is generally greater in graminoids than forbs, the precise difference in harvest efficiency between graminoids and forbs may depend upon the individual plant species and harvest methods.…”
Section: Harvest Efficiency Is Greater In Graminoids Compared To Forbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, in practice, the adoption rate of annual polycultures has remained relatively low [133], and it is difficult to select and devise the optimum cultivation design [134]. Sanford et al [135] could not verify yield advantages of diversity for mixed perennial bioenergy cropping systems. Generally, compared with sole cropping, multispecies systems are potentially more difficult to manage, and require substantial farmer skills and specific research efforts [126].…”
Section: Potentials and Limitations Of Perennial Polyculturesmentioning
confidence: 99%